Study of the Migratory Return: Analysis to the Condition of the Returned Migrant in the Educational and Labor Reintegration and the Entrepreneurship as an Area of Opportunity - Betanzos, Iris E. (European Scientific Journal, ESJ, 2018)
Studies on the educational and labor reintegration of migrants returned to Latin American countries have gained importance due to the economic and social implications of rehabilitation. In this article, the return of the migrant was considered part of the migration process. An exploratory research of publications in different international journals was carried out; when consulting the referenced articles, it was identified that at the time of return the migrant presents and perceives a moral, social, educational and work imbalance. From the deficiencies found in the theoretical lines studied - Educational reinsertion, Labor reintegration - the third theoretical line was included the importance of relating the concept of entrepreneurship as an area of opportunity for returned migrants. The results of the analysis of the studies and theoretical frameworks of international migration, showed great similarities of the phenomenon in different geographical spaces, being an indispensable tool to understand their different forms, evolution and development both in the countries of origin and destination.